2019
DOI: 10.3390/polym11030522
|View full text |Cite
|
Sign up to set email alerts
|

Ethylcellulose in Organic Solution or Aqueous Dispersion Form in Designing Taste-Masked Microparticles by the Spray Drying Technique with a Model Bitter Drug: Rupatadine Fumarate

Abstract: The taste of drugs is an important factor affecting pharmacotherapy effectiveness, and obtaining formulations with acceptable organoleptic properties is still an ongoing issue in pharmaceutical technology. One of the innovative methods of taste masking is preparation of microparticles by the spray drying technique, utilizing polymers with different physicochemical properties. Rupatadine fumarate (RUP) is one of the newest antihistamines, with an innovative and multidirectional mechanism of action, and an extre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…To determine whether the designed particles effectively masked the bitter taste of rupatadine fumarate, three independent methods were used: a human taste panel, an in vitro release test conducted in conditions mimicking the oral cavity environment, and an electronic taste sensing system (electronic tongue). It was clearly confirmed that particles formulated from aqueous dispersions of EC provided a very effective taste-masking barrier [49]. Evaluation of the use of Surelease ® as a barrier membrane coating with pediatric precedence of use on the taste-masking of immediate-release acetaminophen granules was also conducted.…”
Section: Applicability Of Ec In Pharmaceutical Formulationsmentioning
confidence: 92%
“…To determine whether the designed particles effectively masked the bitter taste of rupatadine fumarate, three independent methods were used: a human taste panel, an in vitro release test conducted in conditions mimicking the oral cavity environment, and an electronic taste sensing system (electronic tongue). It was clearly confirmed that particles formulated from aqueous dispersions of EC provided a very effective taste-masking barrier [49]. Evaluation of the use of Surelease ® as a barrier membrane coating with pediatric precedence of use on the taste-masking of immediate-release acetaminophen granules was also conducted.…”
Section: Applicability Of Ec In Pharmaceutical Formulationsmentioning
confidence: 92%
“…Much of the research work on RF is related to the analytical method development. Formulation research includes preparation of its immediate release tablets by QbD approach [12] and as a model drug for taste masking by employing ethyl cellulose [13]. Patents on liquid oral formulations of the drug have been published [14].…”
Section: Introductionmentioning
confidence: 99%
“…The surface morphology of the CPT microparticles was influenced by the amount of EC used, a hydrophobic polymer that is used for film coating or in polymeric matrices, in formulation. Batches manufactured with high EC content produced microparticles with smooth surfaces [55,56]. Conversely, batches produced with low EC content produced microparticles with rough, corrugated surfaces.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 98%